Getting Them Early: Teaching a Critical Perspective on Legal Ethics and Adversarialism in an Introductory LLB Unit at the Queensland University of Technology - Barbara Hamilton (Legal Education Review)
This article will explore two themes using examples taken from my online teaching in a commercial law subject at Murdoch University Law School. The first theme is the need to take seriously a commitment to teaching legal ethics pervasively in law school. The second is the tension between legal and business ethics and the relevance of this issue for the law curriculum. It is my view that teaching legal ethics pervasively entails not only incorporating legal ethics into a majority of law school subjects but also dealing with it in a pervasive manner within those subjects. I suggest that the benefits of the pervasive method are lost both when ethical issues are confined to explicit modules within a subject as well as when ethics teaching is confined to a stand-alone subject in the curriculum. This article explores the demands of being constantly alive to ethical issues in our teaching. It is also my view that law teachers can make productive use of contrasts and comparisons between legal and business ethics, particularly in commercially oriented law subjects. I explore how such a comparative approach may help stimulate student discussion and reflection on professional roles and responsibilities.